Dietary Patterns and Individual Parkinsonian Signs Among Biracial Population of Older Adults. (7th June 2021) - Agarwal, Puja; Tangney, Christy; Zhang, Yanyu; Desai, Pankaja; Halloway, Shannon; Liu, Xiaoran; Barnes, Lisa; Schneider, Julie; Buchman, Aron; Evans, Denis
Abstract: Objectives: Loss of motor function, including parkinsonian signs, is common among older adults. Given limited treatment options, we investigated individual parkinsonian signs in accordance with two dietary patterns -Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) and Mediterranean diet (MedDiet) in older adults. Methods: This cross-sectional observational study included 1496 Chicago Health and Aging Project participants aged 78.5 ± 6.4, 40% female, and 50% Blacks (a subsample of the community cohort, with dietary information (assessed by a validated food frequency questionnaire) and parkinsonian signs assessments done within 2.5 years). The four parkinsonian signs (bradykinesia, gait, tremors, and rigidity) were evaluated using a 26-item modified version of the United Parkinson's Disease Rating Scale (UPDRS) and were averaged to construct a global parkinsonian sign score. Linear (global parkinsonian signs, bradykinesia, and gait score) and logistic (tremors and rigidity (present/absent)) regression models were adjusted for age, sex, race, education, smoking, physical activity, and calories. We further adjusted the models for cardiovascular conditions (diabetes, hypertension, stroke, myocardial infarction). Diet was assessed both as continuous and in tertiles. Results: MIND (T3 vs. T1: β = −0.39, P  < 0.0001) and MedDiet (T3 vs. T1: β = −0.41, P  < 0.0001) scores were associated with a lower global parkinsonian sign score in separate models. Those in the highest tertile of MIND and MedDiet had lower bradykinesia (MIND: T3 vs. T1: β = −0.44, P  = 0.0002; MedDiet: T3 vs. T1: β = −0.38, P  = 0.003) and gait (MIND: T3 vs. T1: β = −0.48, P  = 0.0003; MedDiet: T3 vs. T1: β = −0.61, P  < 0.0001) score than those in the lowest tertile. The MIND diet was associated with lower odds of tremors (T3 vs. T1: OR = 0.70, 95% CI:0.51, 0.95) and rigidity (T3 vs. T1: OR = 0.65, 95% CI:0.47, 0.89). However, MedDiet was associated with lower odds of rigidity (T3 vs. T1: OR = 0.45, 95% CI:0.32, 0.64) but not tremor. All associations were retained when further controlled for cardiovascular conditions. Conclusions: MIND and MedDiet may benefit motor outcomes such as individual parkinsonian signs, including bradykinesia, gait, and rigidity in the aging population. Future studies with longitudinal follow-up are needed. Funding Sources: Michael J Fox Foundation, R01AG021972, R01AG011101